2017
DOI: 10.1016/j.freeradbiomed.2016.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Community metabolic modeling approaches to understanding the gut microbiome: Bridging biochemistry and ecology

Abstract: Interest in the human microbiome is at an all time high. The number of human microbiome studies is growing exponentially, as are reported associations between microbial communities and disease. However, we have not been able to translate the ever-growing amount of microbiome sequence data into better health. To do this, we need a practical means of transforming a disease-associated microbiome into a health-associated microbiome. This will require a framework that can be used to generate predictions about commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…These limitations hinder a systematic and comprehensive study of long term genomic reduction or identification of general principles in the emergence of species interaction. On the other hand, theoretical and computational models have been broadly useful for studying microbial communities [ 22 , 23 ], and indeed several recent studies have used computational models to specifically address the evolution of cooperation [ 24 , 25 ]. Such studies have allowed long time scales to be easily modeled and have produced useful insights into genetic and environmental determinates of cooperation, but tend to explicitly model interaction in a non-mechanistic manner.…”
Section: Introductionmentioning
confidence: 99%
“…These limitations hinder a systematic and comprehensive study of long term genomic reduction or identification of general principles in the emergence of species interaction. On the other hand, theoretical and computational models have been broadly useful for studying microbial communities [ 22 , 23 ], and indeed several recent studies have used computational models to specifically address the evolution of cooperation [ 24 , 25 ]. Such studies have allowed long time scales to be easily modeled and have produced useful insights into genetic and environmental determinates of cooperation, but tend to explicitly model interaction in a non-mechanistic manner.…”
Section: Introductionmentioning
confidence: 99%
“…Our in silico study of this microbial community of probiotics identified a total of 632 unique exogenous metabolites which are potentially required for growth under normal circumstances [ 20 ]. Among them, 62 are essential for all strains, 200 are required by single microbes in the community, and 398 are shared between different strains.…”
Section: Resultsmentioning
confidence: 99%
“…Although our application is specifically designed to work with the KEGG database, similar logic could be used for other databases such as MetaCyc (Caspi et al , 2014). Our tool also does not apply methods such as gap-filling (Thiele et al , 2014; Orth and Palsson, 2010) and metabolic modeling (Orth et al , 2010; Mendes-Soares and Chia, 2017) in its estimates. The goal is not to produce precise measurements of the contributions of the microbiome and host to the abundance of a metabolite.…”
Section: Discussionmentioning
confidence: 99%